MENINGKATKAN KEPATUHAN PAJAK: PERAN SISTEM ADMINISTRASI PAJAK DIGITAL, PERSEPSI ANTI KORUPSI, DAN PENGELUARAN PEMERINTAH - Muttaqin, Ibnu; Risnawati, Heni; Wahyuningsih, Panca (STIE PENA, 2025)
This study analyzes the influence of a digital tax administration system, anti-corruption perceptions, and government spending on tax compliance among Micro, Small, and Medium Enterprises (MSMEs). Tax compliance is crucial in supporting state revenue, particularly from the MSME sector, which is the backbone of the national economy. The quantitative method used in this study was a questionnaire. The sampling technique used in this study was the MSMEs in Tegal City. In total, 128 MSMEs were obtained. The analysis used Multiple regression analysis was performed using SPSS software. The results show that the digital tax administration system has a positive effect on MSME tax compliance, reflecting the importance of digitalization in improving the efficiency and transparency of tax services. Furthermore, anti-corruption perceptions also proved to have a significant effect, indicating that trust in government integrity is a determining factor for tax compliance. Government spending on public services also contributes to tax compliance along with increased perceptions of tax benefits among MSMEs. These findings emphasize the importance of administrative reform, increased transparency, and accountability in tax management to encourage better tax participation in the MSME sector.